2022
DOI: 10.1021/acs.jpclett.2c01708
|View full text |Cite
|
Sign up to set email alerts
|

Protein Condensation at Nanopore Entrances as Studied by Differential Scanning Calorimetry and Small-Angle Neutron Scattering

Abstract: The condensation of globular myoglobin (Mb) at the pore entrances of mesoporous silica (MPS) with a series of pore diameters (4.2, 6.4, 7.7, and 9.0 nm) was examined by differential scanning calorimetry (DSC) and contrast-matching small-angle neutron scattering (CM-SANS) experiments. The DSC measurements were performed to estimate the amount of Mb adsorbed at two different adsorption sites, namely, the pore interior and the pore entrance regions. The CM-SANS measurements were conducted to observe condensation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This results are in agreement with recent publication on myoglobin infiltration and condensation at pores entrance. 13,60 Results of infiltration of glutaminase and amino acid oxidase show an increased overlayer deposition close to the enzyme diameter. In case of urase the infiltration into the structure seems to be hindered and an overlayer thickness similar in value to the enzyme diameter was measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results are in agreement with recent publication on myoglobin infiltration and condensation at pores entrance. 13,60 Results of infiltration of glutaminase and amino acid oxidase show an increased overlayer deposition close to the enzyme diameter. In case of urase the infiltration into the structure seems to be hindered and an overlayer thickness similar in value to the enzyme diameter was measured.…”
Section: Resultsmentioning
confidence: 99%
“…8 Optimal nanopore diameters have been reported for enhancing the stability of the folded structures, [9][10][11] and inhibit irreversible aggregation despite being under protein crowding conditions. [12][13][14] Furthermore, the knowledge of protein location and assembly within a material will contribute to design programmable or multifunctional bio-composite systems inside nanopores and to make nanopore based sensing of protein structures more accurate. 15,16 Mesoporous oxide thin films (MTF) provide a sound platform for the creation of ordered arrays of monodisperse cavities.…”
Section: Introductionmentioning
confidence: 99%
“…41 They also investigated a pore size dependence of Mb stacking using small-angle neutron scattering. 43 Mb molecules stacked at a 64 nm pore in a highly concentrated solution, whereas they aggregated at the entrance of the pores with 75 and 77 nm sizes at low Mb concentrations. The dependence of pore size on the protein adsorption at the equilibrium state is becoming clearer, but there has been little discussion regarding the distribution and release kinetics of proteins in the porous materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Yamaguchi et al revealed that the Mb molecule (3.5 nm in diameter) penetrated mesoporous silica with pore sizes of 3.3 and 5.3 nm, whereas they aggregated or stacked at the entrance of the pore with a size of 7.9 nm . They also investigated a pore size dependence of Mb stacking using small-angle neutron scattering . Mb molecules stacked at a 64 nm pore in a highly concentrated solution, whereas they aggregated at the entrance of the pores with 75 and 77 nm sizes at low Mb concentrations.…”
Section: Introductionmentioning
confidence: 99%